Bolivia and Ecuador: Comparing Social Movements, 1990-2008 - Cruz Rodríguez, Edwin (2012)
This article explains the differences between Indigenous social movements in Ecuador and Boliviaduring the 1990-2008 time period, focusing on pace, intensity, and perseverance. It comparestheir organizational structures, collective action frameworks, and political opportunity structures.